Developmental sequences of squamate reptiles are taxon specific. Issue 5 (20th September 2013) - Andrews, Robin M.; Brandley, Matthew C.; Greene, Virginia W.
SUMMARY Recent studies in comparative vertebrate embryology have focused on two related questions. One concerns the existence of a phylotypic period, or indeed any period, during development in which sequence variation among taxa is constrained. The second question concerns the degree to which developmental characters exhibit a phylogenetic signal. These questions are important because they underpin attempts to understand the evolution of developmental characters and their links to adult morphology. To address these questions, we compared the sequence of developmental events spanning the so‐called phylotypic period of vertebrate development in squamate reptiles (lizards and snakes), from the formation of the primary optic placode to the first appearance of scale anlagen. We used Bayesian phylogenetic ancestral state reconstruction analyses and estimates of Bayesian posterior probabilities of the rank order of developmental events to determine the level of support for phylogenetically associated variation in development. We assessed the amount of variation in event sequences by plotting the proportions of reconstructed ranks (excluding unlikely events, PP < 0.05) associated with each event. Sequence variability was the lowest towards the middle of the phylotypic period and involved three events (allantois contacts chorion, maximum number of pharyngeal slits, and appearance of the apical epidermal ridge [AER]); these events each had only two reconstructed ranks. Squamate clades also differed in the rank order of developmental events. Of the 20 events in our analyses, 12 had strongly supported (PP ≥ 0.95) sequence ranks that differed at two or more internal nodes of the tree. For example, gekkotans are distinguished by the late appearance of the allantois bud compared to all other squamates (ranks 7 and 8 vs. rank 3, respectively) and Serpentes are distinguished by the earlier completion of torsion (rank 3) compared to acrodonts and pleurodonts (ranks 7 and 5, respectively). Clade specific sequences of developmental events mean that investigators should not extend observations on the development on particular squamate species to distantly related taxa for use in comparative studies.